Experience of Using Operated Roofs Abroad - Latipovich, Tabibov Abduvoris (Research Parks Publishing LLC, 2023)
This article analyzes wildlife and architecture, are inextricably linked, and that huge areas of the roofs of industrial, residential and public buildings, underground structures make up an indispensable reserve of cities.